Deciding the feasibility of a given throughput rate in 2-cyclic robotic scheduling - Sáez, Pablo (Theoretical computer science, 2025)
We highlight in this article the relevance of a decision problem in k-cyclic robotic scheduling: deciding whether a certain throughput is feasible or not. Research until now has been focused mainly on the optimization problem (finding the maximum possible throughput). We provide an algorithm for this decision problem in 2-cyclic robotic scheduling that runs in O(n3) time, where n is the number of machines in the production line, and we outline possibilities for further work in this direction.